A day of unfinished mourning: Historicizing commemorative practices of Bleiburg among the Croatian diaspora in Argentina. (December 2020) - Židek, Nikolina
The Croatian post-Second World War diaspora in Argentina developed a specific identity due to the historical context of its exile (the war defeat of the Nazi-aligned Independent State of Croatia, the postwar killings of the defeated troops and the civilians at Bleiburg, Austria, with subsequent death marches in 1945—commonly referred to as "Bleiburg, " and the eventual forced migration) that served as a baseline of its identity across generations. While in Communist Yugoslavia Bleiburg was practically a taboo, the efforts to preserve its memory were carried out by the Croatian political exiles in Argentina as of 1947. This article explores historical memory practices of Bleiburg among the Croatian diaspora in Argentina. Based on an analysis of written, photographic, and audiovisual material, as well as personal testimonies, the study identifies five major periods of memory of the Croatian diaspora in Argentina from 1947 until today. The results of the study show a tendency of double and cumulative victimization: while the first generation was framed as victims of the postwar killings and exile, the post-memory generation also perceives itself as long-term victims of Tito's Yugoslavia because of being born in Argentina. There is an intergenerational transmission of memory throughout the described five periods, and the real change of generations occurs when the survivors perish and new memory entrepreneurs take over the commemorations. The post-memory generation framed commemorations in such a way that they serve to reinforce their identity and enable them to resignify their community history, while maintaining their sense of uniqueness toward both the country where they were born and the country their grandparents were forced to leave.